Literatura polska we Włoszech po 1989 roku - De Carlo, Andrea F. (Tematy i Konteksty, 2024)
The history of Italian translations of Polish literary works is closely linked not only to the development of Italian publishing, but also to a reception that followed partly different paths compared to that of other great European literatures. Undoubtedly a bibliography of Polish works translated in Italy can provide interesting and objective information on the choices made by Italian cultural circles, and in particular on the contribution of polonists and 'polonophiles' in the diffusion of Polish literature in Italy, on the editorial initiatives that have characterized the book industry from 1989 to today, on the function of the translator, who is necessarily responsible for the success or failure of a work and whose figure often does not receive the attention it deserves despite the role played in the context of cultural circulation. The article aims to reveal that ‘presence’ of Polish literary works has profoundly changed – apparently – for the better, thanks also to the work of a new and large generation of Polish scholars and lively young translators, whose interest is mainly oriented towards contemporary Polish literature.